The Effect of Work-life Balance on Work Performance : The Mediating Role of Psychological Contract Breach - Tazkiyah Nur Laili Citra Dewi; Anang Kistyanto (Profesional Muda Cendekia Publishing, 2022)
The purpose of this study was to determine and analyze the impact of work-life balance on work performance mediated by psychological contract breach. This survey is a quantitive approach to 50 employees. Respondents to this survey are as many as 46 employees. The analysis used is Structural Equation Model (SEM) method on Partical Least Square (PLS) supported by smartPLS (v.3.3.7) software. The Likert Scale is used as a measurement scale. The results of the survey show that work-life balance has a significant and positive impact on work performance. In addition, psychological contract breach has an unsignificant impact on work performance, work-life balance has a significant and negative impact on psychological contract breach and psychological contract breach does not mediate a relationship among work-life balance to work performance. USP Minatani Brondong must pay attention to work-life balance and what has been promised to the workers to produce good performance for the company.